INVITRO-PLANT REGENERATION FROM MATURED SEED EXPLANT OF LOCAL AND IMPROVED RICE (ORYZA SATIVA L.) VARIETIES - ZAINAB A, ABUBAKAR,; ADAMU PEACE, (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2022)
Plant tissue cultures of crops are carried out to produce more crops within a short period of time and as well to overcome the demands of food by the fast growing population. Numerous concerns have been centered towards indica rice, for a reason the study aimed at assessing the growth and if possible yield performance of some local rice varieties using invitro plant regeneration method. The study was conducted to observe the regeneration potential and also to establish a suitable in vitro plantlet regeneration protocol from mature seed explant of four rice varieties viz local rice Variety (Maizabuwa and Mai kwalli) and improved rice variety (Nerica and Faro 44). Maizabuwa was the only variety that successfully regenerated by proliferating shoot and root from the rice seed explant while Faro 44, had root development in the MS media under in-vitro condition. After transplanting, only Maizabuwa successfully germinated from the soil and plantlet growth was observed. No variations was observed in growth responses (plant height (cm), number of tillers, number of leaves and leaf area (cm2)) between in-vitro and soil regenerated (potted in soil) Maizabuwa and Faro 44 rice varieties, whereas variation in growth responses measured between the four varieties of rice directly potted in soil media was observed. Soil potted plants showed some significant differences in growth where Maizabuwa and Nerica varieties indicated to contribute to such variation. The study indicate that seeds of Maizabuwa local rice variety can be suggested to farmers if interested in large scale farming as the variety has shown observable tolerance to in-vitro regeneration and as well potted soil media conditions.